2021
DOI: 10.1111/hex.13411
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the expectations, experiences and tensions of refugee patients and general practitioners in the quality of care in general practice

Abstract: Background Refugees and asylum seekers arrive in the Australian community with complex health needs and expectations of healthcare systems formed from elsewhere. Navigating the primary healthcare system can be challenging with communication and language barriers. In multicultural societies, this obstacle may be removed by accessing language‐concordant care. Emerging evidence suggests language‐concordance is associated with more positive reports of patient experience. Whether this is true for refugees and asylu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Parallel to GP interviews we also conducted qualitative interviews with community members from refugee and asylum seeker backgrounds to understand their experiences of general practice in Sydney, Australia. The findings from this component of the study have been published elsewhere (Patel, Muscat, et al, 2021 ). The reporting of this qualitative study follows the consolidated criteria for reporting qualitative research (COREQ criteria; Tong et al, 2007 ).…”
Section: Methodsmentioning
confidence: 69%
See 1 more Smart Citation
“…Parallel to GP interviews we also conducted qualitative interviews with community members from refugee and asylum seeker backgrounds to understand their experiences of general practice in Sydney, Australia. The findings from this component of the study have been published elsewhere (Patel, Muscat, et al, 2021 ). The reporting of this qualitative study follows the consolidated criteria for reporting qualitative research (COREQ criteria; Tong et al, 2007 ).…”
Section: Methodsmentioning
confidence: 69%
“…We analysed data in an iterative manner, using an analytical approach that was both inductive (data‐driven) and deductive (researcher‐driven), based on the research questions, to develop a coding framework to reflect emerging patterns and themes. This process allowed for the data to be triangulated with both existing literature, but also parallel qualitative interviews conducted with refugee and asylum seeker community members (Patel, Muscat, et al, 2021 ). In discussion, all authors identified relationships amongst and between categories to generate themes.…”
Section: Methodsmentioning
confidence: 99%
“…We found that distrust may also be curbed by involving people with whom a trustful relationship already exists, for example, GPs. Furthermore, Patel et al found that using health professionals who speak the refugees' language gave the refugees a feeling of speaking to a trusted person with the same cultural and linguistic background 23 . We argue that trust is central to building culturally appropriate prevention services in which acceptability and thereby accessibility may also be facilitated through intercultural agents.…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, Patel et al found that using health professionals who speak the refugees' language gave the refugees a feeling of speaking to a trusted person with the same cultural and linguistic background. 23 We argue that trust is central to building culturally appropriate prevention services in which acceptability and thereby accessibility may also be facilitated through intercultural agents. Such agents' key roles are to facilitate trust and underpin empowerment by informing about and interacting with health services.…”
Section: Discussionmentioning
confidence: 98%